2004
DOI: 10.1111/j.1365-201x.2004.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucose utilization and inhibition of protein glycation and AGE products by taurine

Abstract: These results underline the potential use of taurine as a therapeutic supplement for the prevention of diabetic pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 37 publications
3
36
0
3
Order By: Relevance
“…A report that long-term dietary supplementation with the amino acid taurine increases survival in streptozotocin-diabetic rats (126) might be provocatively related to the observations that taurine and its precursor hypotaurine can competitively inhibit protein glycation by forming Schiff bases with sugar carbonyls (127) and that taurine can lower levels of glycated proteins in fructose-fed rats (128). Other studies have reported that taurine prevents glucose-induced decrease in erythrocyte Na + /K + and Ca 2+ -ATPase activities (129), lowers cholesterol in genetic GK and streptozotocin-induced diabetic rats fed a high cholesterol diet (130,131), and reduces lipid peroxidation and plasma levels of triglycerides and LDL-cholesterol in streptozotocindiabetic rats (132).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…A report that long-term dietary supplementation with the amino acid taurine increases survival in streptozotocin-diabetic rats (126) might be provocatively related to the observations that taurine and its precursor hypotaurine can competitively inhibit protein glycation by forming Schiff bases with sugar carbonyls (127) and that taurine can lower levels of glycated proteins in fructose-fed rats (128). Other studies have reported that taurine prevents glucose-induced decrease in erythrocyte Na + /K + and Ca 2+ -ATPase activities (129), lowers cholesterol in genetic GK and streptozotocin-induced diabetic rats fed a high cholesterol diet (130,131), and reduces lipid peroxidation and plasma levels of triglycerides and LDL-cholesterol in streptozotocindiabetic rats (132).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Taurin má navíc hypoglykemický efekt (33). Dipeptid karnosin obsahující histidin a β-alanin, snižuje tvorbu malondialdehydu (MDA) a brání lipooxidaci, a tedy snižuje tvorbu ALE a též i AGE (34). Tripeptid glutathion (γ-glutamylcysteinyl glycin, GSH) je významným faktorem udržují-cím rovnováhu buněčných procesů, který zároveň snižuje oxidační stres a redukuje glykaci (31).…”
Section: Přehledové Práceunclassified
“…Diskutiert werden sekundäre Pflanzenstoffe in Form von Polyphenolen wie Curcumin aus dem Gewürz Curcuma (Calabrese et al, 2003) oder Rutin aus Tomaten (Kiho et al, 2004) oder Quercetin aus Thymian (Marimitsu et al, 1995) oder Flavonoide aus der brasilianischen Kamille und aus Mate (Nandhini et al, 2004). Auch von Taurin wird berichtet, dass es in vitro die Glykierung und Akkumulation von AGEs inhibiert (Nandhini et al, 2004).…”
Section: Natürliche Inhaltsstoffe In Lebensmitteln Als Inhibitorenunclassified